Development and validation of UV spectrophotometric procedure for estimation of bifonazole in bulk - Antypenko, L. M.; Gladysheva, S. A.; Korzhova, A. S.; Антипенко, Людмила Миколаївна; Гладишева, Світлана Анатоліївна; Коржова, Алла Станіславівна (Himalayan Pharmacy Institute, Majitar, 2016)
A simple, precise, accurate, reproducible and low cost UV-spectrophotometric method has been developed and validated for the quantification of Bifonazole in bulk. The linearity is found at the 256 nm for 0.0006-0.001% Bifonazole solutions in 0.1 M HCl according to Beer–Lambert–Bouguer law. The determination coefficient is 0.999, LOD - 1.50 μg/mL, and LOQ - 4.54 μg/mL. The exact ready-to-use methodic for quantity determination is proposed, which can be successfully used for determination of Bifonazole in bulk and for future studies in pharmaceutical formulations.
Keywords: Bifonazole; validation; UV-spectrophotometry